Enhanced biomass production and pollutant removal by duckweed in mixotrophic conditions. (December 2020) - Sun, Zuoliang; Guo, Wenjun; Yang, Jingjing; Zhao, Xuyao; Chen, Yan; Yao, Lunguang; Hou, Hongwei
Graphical abstract: Highlights: Duckweed growth under mixotrophy, heterotrophy and photoautotrophy was compared. Duckweed metabolized glucose, fructose, galactose, sucrose and maltose. Mixotrophy was best for biomass production and pollutant uptake. Heterotrophy is a feasible method for starch induction. Mixotrophic-heterotrophic cultivation strategy should enhance starch accumulation. Abstract: Duckweed is a potential biomass source for alternative energy production. This work reports the effects of trophic modes on growth rates, biomass accumulation, and removal rates of pollutant by duckweed. Glucose, fructose, galactose, sucrose, and maltose all supported heterotrophic and mixotrophic growth of duckweed. The mixotrophic growth rate was 4.98 and 6.22 times higher than those in heterotrophic and photoautotrophic conditions, respectively. Notably, mixotrophy produced more biomass than the simple sum of the biomass accumulation during heterotrophy and photoautotrophy. Mixotrophy was also superior in starch and protein production, as well as in removal rates of nutrients and organic carbon from the growth medium. However, the starch content of duckweed grown heterotrophically was 2.06 times higher than in mixotrophy, suggesting a combination of mixotrophy and heterotrophy as an effective strategy for starch-rich biomass production. This study thus provides a paradigm for future studies supporting duckweed-based biomass production and organic wastewater treatment.